2009
DOI: 10.1096/fj.09-144147
|View full text |Cite
|
Sign up to set email alerts
|

Increased adenosine contributes to penile fibrosis, a dangerous feature of priapism, via A 2B adenosine receptor signaling

Abstract: Priapism is a condition of persistent penile erection in the absence of sexual excitation. Of men with sickle cell disease (SCD), 40% display priapism. The disorder is a dangerous and urgent condition, given its association with penile fibrosis and eventual erectile dysfunction. Current strategies to prevent its progression are poor because of a lack of fundamental understanding of the molecular mechanisms for penile fibrosis in priapism. Here we demonstrate that increased adenosine is a novel causative factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 42 publications
(52 reference statements)
1
79
1
Order By: Relevance
“…It has also been shown to promote production of TGF-beta [58]. Recently, it has been demonstrated that adenosine, signaling via A 2B R, stimulates TGF-beta secretion from corpus cavernosum fibroblasts in an autocrine fashion, thereby promoting fibroblast proliferation and increased production of collagen [59]. This represents a common final pathway in hepatic and penile fibrosis.…”
Section: Unique Aspects Of Adenosine Receptor Signaling In Organ Fibrmentioning
confidence: 99%
“…It has also been shown to promote production of TGF-beta [58]. Recently, it has been demonstrated that adenosine, signaling via A 2B R, stimulates TGF-beta secretion from corpus cavernosum fibroblasts in an autocrine fashion, thereby promoting fibroblast proliferation and increased production of collagen [59]. This represents a common final pathway in hepatic and penile fibrosis.…”
Section: Unique Aspects Of Adenosine Receptor Signaling In Organ Fibrmentioning
confidence: 99%
“…[74][75][76] Theophylline, an adenosine receptor antagonist, has consequently been shown to inhibit these adenosine-induced erections. 74,79 These results suggest the possibility that another signaling pathway may represent a potential target for the future prevention and treatment of priapism.…”
Section: Intracavernosal Injectionsmentioning
confidence: 88%
“…TGF-β 1 is a common profibrotic factor that mediates the pathologic process of fibrosis in multiple organs (Matsuoka and Tsukamoto 1990;Wen et al 2010;Lang et al 2011;Samarakoon et al 2012). Matsuoka and Tsukamoto (1990) found that TGF-β 1 plays critical role in pathogenetic role in alcoholic liver fibrogenesis by stimulation of hepatic lipocyte collagen production.…”
Section: Discussionmentioning
confidence: 99%
“…However the intermediate molecule and signaling pathway are unknown. Realizing that TGF-β 1 is a common profibrotic factor which mediates the pathologic process of fibrosis in multiple organs (Matsuoka and Tsukamoto 1990;Wen et al 2010;Lang et al 2011;Samarakoon et al 2012), we hypothesize that TGF-β 1 is responsible for androgen deprivation-induced fibrosis in bladder tissues. To test this hypothesis, firstly we measured the TGF-β 1 mRNA levels Androgen deprivation induced TGF-β production contributes to induction of pro-collagen I mRNA expression level.…”
Section: Tgf-β Is a Signaling Molecule Responsible For Androgen Deprimentioning
confidence: 98%
See 1 more Smart Citation